Computational studies of speech intelligibility in open-plan offices - Witold Mikulski (Nofer Institute of Occupational Medicine, 2019)
Background Noise in open-plan offices, connected with an unintentional hearing of conversations and related distraction of attention, causes annoyance of employees. The article presents the calculated range of speech intelligibility in a selected open-plan office room. Material and Methods The speech transmission index (STI) was examined in a real room of 300 m 3 . The room was equipped with a sound absorbing suspended ceiling, acoustic screens and sound absorbing materials on the walls. Initial tests were conducted in order to verify the assumed computational model from ODEON software, as well as the geometrical and acoustic data describing the room. The verification process consisted of comparing the calculations and measurement results. In the main part of the study, the range of speech intelligibility was calculated for several locations of the speech source, i.e., areas in which the STI > 0.5. Results The results of the calculations and the results of the measurements of physical quantities, characterizing the acoustic properties of the open-plan office room (including STI), showed good agreement. For speech emission, the ranges of speech intelligibility were determined on several work stations. Conclusions The use of calculation methods to simulate the sound field in open-plan office rooms is possible when the calibration of the room model is initially performed. Determination of the speech intelligibility range provides important information about the distance of negative acoustic interactions between work stations. This range can be used to determine the interaction between work stations or to assess various technical solutions to reduce the negative interaction. Med Pr. 2019;70(3):327-42